2018
DOI: 10.1534/g3.117.300483
|View full text |Cite
|
Sign up to set email alerts
|

Joint Analysis of Strain and Parent-of-Origin Effects for Recombinant Inbred Intercrosses Generated from Multiparent Populations with the Collaborative Cross as an Example

Abstract: Multiparent populations (MPP) have become popular resources for complex trait mapping because of their wider allelic diversity and larger population size compared with traditional two-way recombinant inbred (RI) strains. In mice, the collaborative cross (CC) is one of the most popular MPP and is derived from eight genetically diverse inbred founder strains. The strategy of generating RI intercrosses (RIX) from MPP in general and from the CC in particular can produce a large number of completely reproducible he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Model organism GRPs have been precisely designed to offer increased statistical power (e.g., mouse [24][25][26], Drosophila [27], yeast, see following text) and an opportunity for systems genetics discovery with in vivo correlation and validation capabilities. One of the pillars of model organism genetic mapping studies has been the analysis of pairwise crosses between two genetically divergent founder strains ( Figure 1A).…”
Section: Cell Panels From Model Organism Grpsmentioning
confidence: 99%
“…Model organism GRPs have been precisely designed to offer increased statistical power (e.g., mouse [24][25][26], Drosophila [27], yeast, see following text) and an opportunity for systems genetics discovery with in vivo correlation and validation capabilities. One of the pillars of model organism genetic mapping studies has been the analysis of pairwise crosses between two genetically divergent founder strains ( Figure 1A).…”
Section: Cell Panels From Model Organism Grpsmentioning
confidence: 99%
“…By mating different CC strains, we can generate recombinant inbred inter-crosses (CC-RIX) (Zou et al 2005;Schoenrock et al 2018). CC-RIX are outbred but their genomes are completely reproducible (by mating their parental CC strains) and thus are an intriguing model of the genetic diversity akin to that in human populations (Zou et al 2005;Liu et al 2018). The genetic diversity of CC-RIX enables the study of parent-of-origin effects and their phenotypic characterization has demonstrated that there are strong strain effects in some measures (Crowley et al 2015;Schoenrock et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…CC-RIX are outbred but their genomes are completely reproducible (by mating their parental CC strains) and thus are an intriguing model of the genetic diversity akin to that in human populations (Z ou et al . 2005; L iu et al . 2018).…”
Section: Introductionmentioning
confidence: 99%